2008
DOI: 10.1002/ptr.2707
|View full text |Cite
|
Sign up to set email alerts
|

Lipid extract from completely sporoderm‐broken germinating Ganoderma sinensis spores elicits potent antitumor immune responses in human macrophages

Abstract: Ganoderma sinensis has been used widely in Oriental countries for the prevention and treatment of various diseases including cancer. Previous studies have shown that the lipid extract from Ganoderma exhibits direct cytotoxicity against tumor cells. Here, it is reported that the lipid extract from germinating G. sinensis spores, at lower concentrations that have no direct tumoricidal activity, induce potent antitumor immune responses in human monocytes/macrophages. Upon stimulation with the lipid extract, monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…More recently, we have reported GLE exert antitumor activities by direct tumoricidal effects or indirectly by activating monocytes/macrophages (Zhang et al, 2009). However, to date, the ability of GLE to antagonize transforming growth factor beta 1 (TGF-β1)-mediated changes associated with EMT in CCA cells has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we have reported GLE exert antitumor activities by direct tumoricidal effects or indirectly by activating monocytes/macrophages (Zhang et al, 2009). However, to date, the ability of GLE to antagonize transforming growth factor beta 1 (TGF-β1)-mediated changes associated with EMT in CCA cells has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, the highest antioxidant activity of crude lipids of several macroalgae species extracted with hexane may be due to the presence of many substances such as carotenoids, soluble lipids, phenolic compounds, steroids and terpenoids [31] The mean (n=3) difference was significant at P ≤ 0.05 Table 7: Antioxidant activity of marine algae crude lipids assessed by DPPH radical. [25] found that the Spirulina platensis lipids exhibited free radical scavenging activity (from 21 to 27%) against DPPH with various degrees.…”
Section: Antioxidant Activity Of Marine Algal Crude Lipid Extractsmentioning
confidence: 99%
“…20,21 In the GSL, many fatty acids and ergosterol have been identified and demonstrated to exert anticancer activity and reduce drug-induced cell damage and apoptosis. 23,24,27,28 Here, we further investigate the protective effects of GSL on bone marrow cells against the cytotoxicity of chemotherapeutic agents.…”
Section: Gsl Attenuates the Cytotoxicity Of Ctx To The Hematopoiesimentioning
confidence: 99%
“… GSL concentrates all the bioactive components of the spores, but with much higher bioactivities than the whole spores . Like the fruiting bodies and spores, GSL has been demonstrated to possess immunomodulatory and anticancer effects . However, it is still unclear whether GSL can benefit cancer patients through attenuation of the side effects of chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation